Developing augmented reality novel games as English learning media for reading narrative texts - Khoirunisa, Hajar; Floriasti, Tri Wahyuni (Jurnal Inovasi Teknologi Pendidikan, 2023)
Incorporating augmented reality (AR) into education is increasingly vital for fostering engagement and interactivity, particularly in language learning, where narrative text plays a central role. The objectives of this study were to (1) ascertain the participants' target demands, (2) analyze their English-language learning needs, and (3) create an augmented reality novel game as a teaching tool for narrative text. This research and development project (RD) was conducted. Junior high schoolers were the subjects; they were 15 males and 17 females. This study was done using a 4-D model. Participants were given questionnaires to complete, and an English teacher was interviewed as part of the need analysis. The instruments used to collect the data were the needs analysis questionnaire, interview guidelines, expert judgment rating scale, and student review questionnaire. The result of this study is an augmented reality novel game as English learning media, which was created after taking into account the findings of the needs analysis, professional opinion, and student evaluation. It consists of narrative texts in general and augmented reality books that serve as instances of narrative texts. The developed media's overall average score was 3.65. The created interactive learning multimedia was therefore categorized as suitable. According to the students' review findings, most augmented reality novel games are excellent and appropriate.